Between world history and state formation: new perspectives on Africa’s cities - (:unkn) unknown (My University, 2011)
The dramatic urban change taking place on the African continent has led to a renewed and controversial interest in Africa’s cities within several academic and expert circles. Attempts to align a growing but fragmented body of research on Africa’s urban past with more general trends in urban studies have been few but have nevertheless opened up new analytical possibilities. This article argues that to move beyond the traps of localism and unhelpful categorizations that have dominated aspects of urban history and the urban studies literature of the continent, historians should explore African urban dynamics in relation to world history and the history of the state in order to contribute to larger debates between social scientists and urban theorists. By considering how global socio-historical processes articulate with the everyday lives of urban dwellers and how city-state relationships are structured by ambivalence, this article will illustrate how historians can participate in those debates in ways that demonstrate that history matters, but not in a linear way. These illustrations will also suggest why it is necessary for historians to contest interpretations of Africa’s cities that construe them as ontologically different from other cities of the world.
Keywords: African Research